Finding the impact of information sources a study on the political information efficacy and voting behavior of Filipino young voters in Metro Manila - Del Mundo, Rafael Joseph C. (School of Library and Information Studies, University of the Philippines, Diliman, 2019)
Young voters are an important voting bloc, especially in the Philippines because they not only hold a significant portion of the voting population, but they also represent the future voting culture of the country. In this regard, it is ideal that young voters are well-informed about election-related activities such as knowing about the profile and platforms of political candidates, schedule of the elections, the actual process of registration and voting, and many other important things. Consequently, knowing about one's confidence in their political knowledge is essential for effective engagement and participation in the election. It is in this light that this study focused on determining the impact of election information sources to young voters by identifying sources that are frequently use, reliable and influential. Furthermore, this study determined the Political Information Efficacy (PIE) or the confidence of young voters in their political knowledge as well as their voting behavior of information sources to the PIE and voting behavior of Filipino young registered voters was also one of the focus of this study.